2008
DOI: 10.1167/iovs.07-0809
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Induction and Three-Dimensional Two-Photon Imaging of Conjunctiva-Associated Lymphoid Tissue

Abstract: This study introduces a novel mouse model for functional investigations of CALT. Topical stimulation with C. trachomatis or ovalbumin/cholera toxin B reliably leads to CALT generation at the nictitating membrane. The use of two-photon microscopy enables groundbreaking 3-D and, in the future, intravital 4-D investigations of immunologic processes initiated in CALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…The infiltrating inflammatory cells manifest an orange color, with high fluorescence intensity at longer wavelength (530 AE 21 nm). 16 Most of these cells show parallels with the characteristics of lymphocytes including a small round or oval shape and a thin rim of cytoplasm surrounding the dark round nucleus, 22 as can be found in the H&E-stained images [ Fig. 3(b)].…”
Section: Visualization Of Multiple Pancreatic Components During Chronmentioning
confidence: 80%
See 2 more Smart Citations
“…The infiltrating inflammatory cells manifest an orange color, with high fluorescence intensity at longer wavelength (530 AE 21 nm). 16 Most of these cells show parallels with the characteristics of lymphocytes including a small round or oval shape and a thin rim of cytoplasm surrounding the dark round nucleus, 22 as can be found in the H&E-stained images [ Fig. 3(b)].…”
Section: Visualization Of Multiple Pancreatic Components During Chronmentioning
confidence: 80%
“…20,21 Consequently, different biochemical constituents of cellular or extracellular origins with various emission wavelengths can be detected through multiple channels, which enables simultaneous identification of different tissue components. 16,22,23 Using this method, stromal collagen, which is the major source of SHG signals in extracellular matrix, has been recognized from cellular components. [24][25][26] Lymphatic cells have been distinguished from the other gastric tissue types due to a broad emission that possibly originates from phospholipids, known to be a significant component of lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study revealed the existence of follicles in the nictitating membrane of mouse conjunctiva and their characteristic plasticity in terms of size and numbers after conjunctiva OVA challenge (35,36). Furthermore, Steven et al (37) also showed induction of CALT in 70% of mice by external application of Chlamydia trachomatis serovar C or a solution of OVA and B subunit of CT. It seems likely that CALT could be another candidate as an inductive site for eyedrop vaccination.…”
Section: Discussionmentioning
confidence: 95%
“…In the laboratory mouse, the nictitating membrane (plica semilunaris) has been reported to contain organized lymphoid tissue (34). Although the murine CALT was rarely present under normal conditions, the direct administration of Chlamydia and nonmicrobial antigens into eyes increased the incidence (34,39). Tears are consistently secreted to wet the conjunctiva and cornea, and leaked to the nasal cavity via the lacrimal canaliculi, lacrimal sac, and nasolacrimal duct.…”
Section: Methodsmentioning
confidence: 99%